ANALISIS KOMPETENSI, KEPUASAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA DI KANTOR PELAYANAN PAJAK DAERAH (KPPD) BATAM DINAS PENDAPATAN DAERAH PROVINSI KEPULAUAN RIAU - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to determine the direct effect of job satisfaction on job motivation, direct influence of work motivation on employee performance, direct influence of competence on employee performance, direct influence of job satisfaction on employee performance, indirect influence that is competence to performance Employees through work motivation, indirect influence of job satisfaction on employee performance through work motivation at the Regional Tax Service Office (KPPD) Batam Revenue Service Provincial Riau Islands Province. The number of samples used in this study is 51 samples. The research method used is a scientific method with a quantitative paradigm that is research conducted is research using numerical data or numbers, processing and data analysis using path analysis with SPSS sidware tool Version 21. The results of this study found that competence has a positive and significant influence on work motivation. Job satisfaction has a positive and significant effect on work motivation with. Competence has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Motivation of work has a positive and significant effect on employee performance. Competence has positive and insignificant effect on employee performance through work motivation. This means that work motivation is not variable intervening in mediating the relationship of competence on employee performance, job satisfaction has a positive and significant effect on employee performance through work motivation. This means that the motivation of work as an intervening variable in mediating the relationship of job satisfaction on the performance of employees at the Regional Tax Service Office (KPPD) Batam Regional Revenue Service Riau Islands Province.